INTERNATIONAL AND REGIONAL ORGANIZATION: ORGANIZATIONS AND THEIR ROLES IN MARITIME DELIMITATION OF THE INDIAN OCEAN - Oktavia Ajeng Kartika Dewi (Problematika Hukum, 2021)
Freedom of opinion, especially on social media, is currently widely misunderstood and misused by society, because the exercise of the right to freedom of expression is a matter of society many people commit acts that turn into insults, accusations without evidence, or evidence defamation that causes harm to certain individuals. Problems in research include how the law regulates crimes and violations of the abuse of the right to freedom of opinion on social media and what criminal sanctions are for criminal acts of defamation under the guise of freedom of expression. Method used In preparing this article, the author used a qualitative approach by looking at it from a normative juridical perspective. This law research is based on legal principles, legal systematics, and legal synchronization both horizontally and vertically. This data collection was obtained from previous journal/paper references. This research concludes that freedom of Opinion is not absolute freedom, but opinion must be appropriate to ethics and norms in society and by legal regulations without harming parties.Keywords: Criminal acts; Defamation; Freedom of expression